Penetrating soft palate injury during nasotracheal intubation. Issue 2 (23rd August 2016) - Ayub, Arshad; Pillai, Meera; Singh, Umesh
Summary: Nasotracheal intubation is generally a safe procedure for securing a definitive airway prior to oropharyngeal surgery. However it is associated with specific injuries that range from minor mucosal injury, to retrophayngeal perforation leading to death. We report a rare case of soft palate perforation during conventional nasotracheal intubation and discuss measures to avoid its occurrence.